The effect of different harvest period on fruit quality and phytochemical properties of short and day neutral strawberries - Onur Saraçoğlu; Mustafa Özgen (Turkish Journal of Agriculture: Food Science and Technology, 2015)
In this study, the effect of different harvest period on fruit quality and phytochemical properties of short and day neutral strawberries was investigated. For this purpose, two day-neutral ('Fern', 'Kabarl') and four short day ('Camorosa', 'Sweet Charlie', 'Rubygem' and 'Festival') strawberry varieties were harvested at three different harvest period. Harvested fruits were analysed 15 and 30 days intervals for short and day-neutral varieties. Pomological analysis such as fruit size, firmness, fruit weight, titratable acidity (TA), total soluble solids (TSS), pH and total anthocyanin, total phenolic content and antioxidant capacity were studied. Results of the present study indicated that fruits from later harvest periods displayed smaller fruit size, lower pH and TSS content but higher TA and fruit firmness. Also, both short and day neutral varieties have higher phytochemical content at later harvest period in terms of total phenolics, total anthocyanin and antioxidant capacity.